What makes an epidemic a disaster: the future of epidemics within the EM-DAT International Disaster Database - Margo Tonnelier; Damien Delforge; Regina Below; Juan Armando Torres Munguía; Claude Saegerman; Valentin Wathelet; Joris A. F. van Loenhout; Niko Speybroeck (BMC Public Health)
Abstract Background Reporting on and monitoring epidemics is a public health priority. Several initiatives and platforms provide epidemiological data, such as the EM-DAT International Disaster Database, which has 1525 epidemics and their impact reported since 1900, including 892 epidemics between 2000 and 2023. However, EM-DAT has inconsistent coverage and deficiencies regarding the systematic monitoring of epidemics data due to the lack of a standardized methodology to define what will be included under an epidemic disaster. Methods We conducted a sequential study that included an online survey of experts in infectious diseases, public health emergencies, and related data, followed by committee discussions with disaster experts. This approach aimed to identify appropriate definitions and entry criteria for archiving disease outbreak events. Results The survey had 21 respondents from universities and international organizations, with experts primarily specialized in infectious disease surveillance. Experts agreed that epidemics should be considered as disasters. Experts cited challenges in defining epidemic thresholds. However, they proposed pathogen-based criteria and agreed that disruption to society, especially to the healthcare system, serves as a determinant of epidemic disasters. The experts favored deaths and confirmed cases as key indicators, alongside suggestions on refining EM-DAT's entry criteria and improving epidemic impact assessment. Discussion This article offers valuable insights into epidemic disasters, a topic previously underdefined in the literature, thereby enhancing understanding for policymakers and public health professionals.